2022
DOI: 10.3390/biomedicines10092070
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Nanoparticles towards MMP9 for Controlling Cardiac ECM after Myocardial Infarction: A Predictive Experimental-Computational Chemistry Investigation

Abstract: The recent advances in nanotechnology are revolutionizing preventive and therapeutic approaches to treating cardiovascular diseases. Controlling the extracellular matrix metalloproteinase (MMP) activation and expression in the failing human left ventricular myocardium represents a significant therapeutic target for heart disease. In this study, we used molecularly imprinting polymers (MIPs) to restore the correct balance between MMPs and their tissue inhibitors (TIMPs), and explored the potential of this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In this study, we found that MMP9 and GNLY , as two immune-related genes with the most significant differences in expression, showed consistent trends of expression changes in early serum of STEMI patients with previous research conclusions [ 16 , 17 ]. Matrix metalloproteinases(MMPs) constitute a group of enzymes responsible for extracellular matrix degradation, significantly impacting myocardial remodeling [ 18 ]. Specifically, MMP9 plays a role in the inflammatory response, fibrosis, and angiogenesis following AMI [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that MMP9 and GNLY , as two immune-related genes with the most significant differences in expression, showed consistent trends of expression changes in early serum of STEMI patients with previous research conclusions [ 16 , 17 ]. Matrix metalloproteinases(MMPs) constitute a group of enzymes responsible for extracellular matrix degradation, significantly impacting myocardial remodeling [ 18 ]. Specifically, MMP9 plays a role in the inflammatory response, fibrosis, and angiogenesis following AMI [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases(MMPs) constitute a group of enzymes responsible for extracellular matrix degradation, significantly impacting myocardial remodeling [ 18 ]. Specifically, MMP9 plays a role in the inflammatory response, fibrosis, and angiogenesis following AMI [ 18 ]. Previous research has consistently demonstrated elevated MMP9 levels in the serum of AMI patients, correlating with an unfavorable prognosis [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some presented studies the population of patients was larger, but in others it was comparable. There are many factors that can contribute to differences in MMP expression, including underlying disease, medication, acute illnesses, and carcinoma [24,25]. The expression of MMPs and TIMPs would require further investigation on a wide population of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Short or in vacuum MD simulations have been used to evaluate monomer arrangements in pre-polymerization complexes for diverse molecular targets, such as creatinine, microcystin-LR, carbamate moieties, melamine, acetamide, 17-β-estradiol, , and norfloxacin, among others. Recently, more realistic settings for MD simulations, including explicit solvent molecules, counterions, and multiple monomer compositions, have been applied to address the recognition of various biomolecular targets, including monosaccharides, hormones, and proteins. , These advances raise the opportunity of using MD simulations to optimize the design of molecularly imprinted materials for TC recognition, using more complex and diverse monomer mixtures than those so far reported experimentally to achieve binding sites with an enhanced affinity toward the target.…”
Section: Introductionmentioning
confidence: 99%